Innovative Approaches for Enhancing the 21st Century Student Experience : Final Report. - Coates, Hamish; Kelly, Paula; Naylor, Ryan; Borden, Victor (Australia, Dept of Education and Training, 2017)
Final report from a project that built capacity of higher education institutions by developing new perspectives and approaches for enhancing the student experience. To effectively manage the student experience, institutions must understand who students are and what they expect from higher education. Students have changed in the 21st century and institutions need to understand and do different things to enhance their experience. Much current work has conceptual and technical limitations and is failing to deliver. This project steps ahead in both substantive and methodological ways. Through literature/context reviews and fieldwork it built new conceptualisations of Australia's undergraduate students which go beyond stereotypes, generalities and dated assumptions. Through a scan of institutional practices it identified new and under-utilised empirical options for understanding and enhancing the 21st century student experience. It brings these developments together into a model and enhancement framework.